More publicly funded research, more knowledge spillovers, more economic growth? An empirical analysis for German regions - Jonathan Eberle; Thomas Brenner; Timo Mitze (Philipps-University Marburg, Department of Geography, 2018)
This paper deals with the effects of publicly funded research on regional technological progress and economic growth. We adopt a system approach and investigate the effects on all regional input factors and output by means of a flexible spatial panel VAR (SpPVAR) model. This allows us to deal with the evolutionary nature of regional dynamic processes. We further extend the existing empirical literature on the role of publicly funded research for economic development by differentiating between public research activities conducted by universities, technical colleges (Fachhochschulen) and non-university research institutes. The empirical results show that an increase in (public) third-party funds to technical colleges leads to positive effects on regional investment and employment rates as well as the human capital stock. We also find a positive link between the publication rate of non-university research institutes and regional investment and employment rates. Furthermore, an overall increase in combined public third-party funding of universities and technical colleges affects regional patent activities, the employment rate and output positively.
Keywords: C33; I23; I25; R11; O38; O47; 330; regional economic growth; publicly funded research; production function; factor inputs; multiple equation (SpPVAR) models; impulse-response functions